Assessing the effectiveness of a pilot test of a brief art-based mindfulness task on appraisal - Ben Morris; Rosemary O’Kello (Cogent Psychology)
Mindfulness practice has been proposed as enabling an individual to purposefully increase attention enabling the individual to be more present in the moment, open-minded and accepting. As such mindfulness practice may offer an important mechanism to promote positive psychological health and wellbeing through changes to the stress appraisal process. The aim of this study was to investigate the impact of a simple mindfulness drawing task on dimensions of psychology instrumental in appraisal and health. 65 participants were allocated to one of two conditions (Shambala colouring, Control). The mindfulness group was found to report significantly higher levels of observational ability and non-judgement (p < 0.05) amongst several other differences. This work focused upon the claim of effectiveness of a brief mindfulness task to modify mindfulness focused psychological variables.